Divergent estimates of the ratio between Na+-Ca2+ current densities in t-tubular and surface membranes of rat ventricular cardiomyocytes - Pásek, Michal; Šimurda, Jiří; Bébarová, Markéta; Christé, Georges (Journal of cell science, 2021)
The ratio between Na+-Ca2+ exchange current densities in t-tubular and surface membranes of rat ventricular cardiomyocytes (JNaCa-ratio) estimated from electrophysiological data published to date yields strikingly different values between 1.7 and nearly 40. Possible reasons for such divergence were analysed by Monte Carlo simulations assuming both normal and log-normal distribution of the measured data. The confidence intervals CI95 of the mean JNaCa-ratios computed from the reported data showed an overlap of values between 1 and 3, and between 0.3 and 4.3 in the case of normal and log-normal distribution, respectively. Further analyses revealed that the published high values likely result from a large scatter of data due to transmural differences in JNaCa, dispersion of cell membrane capacitances and variability in incomplete detubulation. Taking into account the asymmetric distribution of the measured data, the reduction of mean current densities after detubulation and the substantially smaller CI95 of lower values of the mean JNaCa-ratio, the values between 1.6 and 3.2 may be considered as the most accurate estimates. This implies that 40 to 60% of Na+-Ca2+ exchanger is located at the t-tubular membrane of adult rat ventricular cardiomyocytes.
Keywords: Animals; Sodium; Heart Ventricles; Myocytes, Cardiac; srdeční komory; Na-Ca exchanger; Membrane current density; t-tubules; Monte Carlo simulation; Sodium-Calcium Exchanger; vápník; Cardiac myocyte; Sarcolemma; Calcium; sodík; krysa rodu Rattus; sarkolema; pumpa pro výměnu sodíku a vápníku; zvířata; Log-normal distribution; Rats; kardiomyocyty